Construction of Infinitely Many Models of the Universe on the Riemann Hypothesis. Issue 2 (October 2016) - Shukla, Namrata
Abstract : The aim of this note is to remove an implausible assumption in Moser's theorem[1] to establish our Theorem 1 which gives a lower estimate for the sum p + c 2 ρ on Riemann hypothesis. Corollary 1 gives a rather plausible construction of infinitely many models of universe with positive density ρ and pressure p since it makes use of the state equation in the form of an inequality.